Face zit together - Chew, Ashley Yue Lieng (2019)
Face Zit Together is the first local public health communication campaign that aims to reduce the negative attitudes towards acne sufferers, who suffer from moderate to severe facial acne, amongst adolescents aged 12 to 17 in Singapore. Through school talks with dermatologists from National Skin Centre, exhibitions, and social media outreach, Face Zit Together hopes to educate adolescents about acne, and encourage them to be kind and gracious to each other by not teasing those with moderate to severe acne. The campaign is initiated by four final year undergraduates from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. Face Zit Together’s campaign strategies are guided by primary research, including qualitative pre-campaign interviews, quantitative pre and post-campaign surveys, and secondary research from various scientific studies. Insights about the problem and target audience were highlighted and addressed in the campaign message, strategies and tactics. Pre-campaign research findings showed that majority of the respondents have a low level of knowledge regarding the misconceptions of acne and have an unfavourable attitude towards moderate to severe acne sufferers. Thus, the campaign focused on two key messages, “everyone plays a crucial role in creating an accepting environment for people with moderate/severe acne” and “acne does not define who that person is”. A detailed post-campaign evaluation of Face Zit Together includes a post-campaign survey evaluation, engagement on social media platforms and media monitoring. The campaign limitations, recommendations and future directions are highlighted in this section.